Gambaran Pengetahuan Tentang Psychological First Aid Pada Relawan Bencana - Sitti Rahma Soleman; Salsabilla Az Zahra; Frinska Angelique Sandra (PT.Mantaya Idea Batara, 2024)
Geographically, Indonesia is a country with a tropical climate with quite extreme changes in weather, temperature and wind direction, making it very vulnerable to hydrometeorological disasters such as floods and landslides. Disaster events have an impact on the physical and even psychological conditions of individuals, families and communities. Apart from that, disasters impact stress and traumatic experiences on their victims. One of the disaster management efforts is post-disaster recovery, including restoring the psychological condition of disaster survivors. First aid efforts can be given to physical and psychological problems so as not to cause trauma or prolonged psychological impacts. One way that can be done is Psychological first aid (PFA), which is a series of interventions to help overcome the mental health problems of someone experiencing a crisis due to a disaster. This intervention needs to be known and applied by disaster volunteers. The aim of this research is to determine the level of knowledge about Psychological First Aid among disaster volunteers. This research was conducted March – July 2023. The population used in this research were all disaster volunteers. The sampling technique used was purposive sampling. The research results showed that 11 people (40.7%) had good knowledge and 16 people (59.3%) respondents had sufficient knowledge. These results show that the percentage between respondents with good knowledge and respondents with sufficient knowledge has a slight difference. This is influenced by several factors, namely education, age, gender, experience as a volunteer, and having attended PFA training. Looking at the existing results, PFA training is also a factor because following this training broadens the volunteers' insight regarding psychological first aid.